Type I interferons in innate immunity to viral infections - Biron, Christine (Henry Stewart Talks, 2009)
Evolving immune response, Interferons, Antiviral effects, IFNalfa/beta induction, Role of IFNalfa/beta in fighting off viruses and infection, Activation of immune response cascades during viral challenges, Immunoregulation, NK cells during viral infections, Innate lymphocytes in defense, Regulation of NK cell responses by IFNalfa/beta and IL-12, IFN signaling, STAT1 in defense against infection, Kinetics of cell and cytokine responses to LCMV infections, STAT expression in NK cells, Type 1 IFN receptor association, Gene expression and protein-protein interactions for regulating type 1 IFN effects, Interferon treatment, Interferon ablation